Semaphorin 3F induces colorectal cancer cell chemosensitivity by promoting P27 nuclear export - Tao, Miaomiao; Ma, Hongbo; Fu, Xiaoyuan; Wang, Cancan; Li, Yanyan; Hu, Xiaoqiao; Lv, Renming; Zhou, Gendou; Wang, Jun; Liu, Ruyan; Zhou, Meiyu; Xu, Guofa; et al. (Frontiers in Oncology, 2022)
Colorectal adenocarcinoma (CRC) is the third most common malignancy worldwide. Metastatic CRC has a poor prognosis because of chemotherapy resistance. Our previous study demonstrated that semaphorin 3F (SEMA3F) signaling may contribute to reversing chemotherapy resistance in CRC cells by reducing E-cadherin and integrin αvβ3 expression levels. Another study showed that upregulation of p27 significantly increase the expression of E-cadherin and integrin. This study aimed to evaluate the effect of SEMA3F on P27 and whether it can reverse resistance in CRC cells. We compared the chemosensitivity of human colorectal cancer cell lines with different SEMA3F expression levels to 5-Fu through cell experiment and animal experiment. Then the interaction between SEMA3F and p27 and its possible mechanism were explored by Western Blot, immunofluorescence and immunocoprecipitation. We also compared the disease-free survival of 118 CRC patients with high or low expression of SEMA3F.The results showed that overexpresstion of SEMA3F enhanced the chemotherapy sensitivity and apoptosis of CRC cells in vitro and in vivo. Among 118 postoperative CRC specimens, the disease-free survival of patients with positive SEMA3F expression was significantly longer than that with negative SEMA3F expression after adjuvant treatment. Upregulation of SEMA3F in multicellular spheroid culture (MSC) could increase p27 phosphorylation at serine 10 (Ser10), subsequently promote the cytosolic translocation of P27. Overall, our results reveal a novel molecular mechanism: SEMA3F mediates the degradation of p27 and regulates its subcellular localization to enhance chemosensitivity to 5-Fu in CRC cells, rather than inhibits p27 expression.